Site selection and soil fertility management by the Outer Baduy People (Banten, Indonesia) in maintaining swidden cultivation productivity - JOHAN ISKANDAR; BUDIAWATI S. ISKANDAR; RUHYAT PARTASASMITA (Biodiversitas Journal of Biological Diversity, 2018)
Iskandar J, Iskandar BS, Partasasmita R. 2018. Site selection and soil fertility management by the Outer Baduy People (Banten, Indonesia) in maintaining swidden cultivation productivity. Biodiversitas 19: 1334-1346. The Outer Baduy people heavily depend on swidden cultivation for subsistence. They grow rice in the uplands every year based on their calendar. The cropping calendar and calendar of social events are often closely interlinked. There is also traditional wisdom for conservation of land and forest such as the zonation for land use system. The Outer Baduy swidden land productivity is mainly determined by the time period of forest fallow relative to that of the crops. The long-term success of the Outer Baduy swidden cultivation depends on how well the fallow period restores or maintain soil fertility. The aim of this research was to study the local knowledge of Outer Baduy of soil categories and soil fertility and the management of soil fertility in their traditional practice of swidden cultivation. The method used in this study was the qualitative one, applying observation and in-depth interviews to collect the primary data. In addition, soil analysis was conducted by the Laboratory of Soil, Faculty of Agriculture, Padjadjaran University, Sumedang, Indonesia. The results of this study showed that the soils are classified by the Outer Baduy based on color, water content, stoniness or rock parent material, and humus content. To maintain soil fertility in the swidden cultivation, the Outer Baduy people have developed some strategies, such as determining appropriate fallow time period, applying zero tillage, and planting legume crops in both the swidden fields and the fallow land. Traditionally, because the Outer Baduy are forbidden to use inorganic fertilizers, the length of fallow period and kind of vegetation succession have an important role in maintaining soil fertility.